2020
DOI: 10.1108/tqm-01-2020-0016
|View full text |Cite
|
Sign up to set email alerts
|

Innovation diffusion in tourism: how information about blockchain is exchanged and characterized on twitter

Abstract: PurposeTechnological innovations provide huge opportunities to expand and revolutionize the scope of products and services offered. This is particularly true for tourism, which is undergoing significant changes due to the development of new technologies. The level of technology diffusion depends on several factors like the exchange of information among peers, and the attitude and shared perception among the contributors. The aim of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 103 publications
0
10
0
1
Order By: Relevance
“…Our literature review further revealed several dimensions of blockchain-related consumer behaviour that have already been investigated, such as individuals' technology adoption (Schuetz & Venkatesh 2020;Treiblmaier et al 2020), consumers' blockchain-related information sharing (Bolici et al 2020), and -perhaps most importantly -consumer participation (Fell et al 2019).…”
Section: Rq2: How Can Service Organizations Enhance Consumers' Trust In Blockchain Applications and How Does This Influence Their Usage Bmentioning
confidence: 82%
“…Our literature review further revealed several dimensions of blockchain-related consumer behaviour that have already been investigated, such as individuals' technology adoption (Schuetz & Venkatesh 2020;Treiblmaier et al 2020), consumers' blockchain-related information sharing (Bolici et al 2020), and -perhaps most importantly -consumer participation (Fell et al 2019).…”
Section: Rq2: How Can Service Organizations Enhance Consumers' Trust In Blockchain Applications and How Does This Influence Their Usage Bmentioning
confidence: 82%
“…Bolici et al (2020) analyze discussions about blockchain and tourism on Twitter. They highlight that the public interest in this specific topic is strong and positive.…”
Section: Discussionmentioning
confidence: 99%
“…In financial sectors, in addition to supporting cryptocurrencies, it offers an opportunity for entrepreneurs who want to create value-reducing financial exclusion (Larios-Hern andez, 2017). Bolici et al (2020) analyze discussions about blockchain and tourism on Twitter. They highlight that the public interest in this specific topic is strong and positive.…”
Section: Blockchain Potential In Business Models and Supply Chainmentioning
confidence: 99%
“…Born as physical events, hackathons are moving more and more virtually by inviting and engaging masses of participants simultaneously from across different geographies and time zones, pushed by the rise of the platform economy that drives the improvement of the online presence, the enhancement of interactions and the development of networking structures as well as digital collaborations (Acciarini et al , 2021; Bolici et al , 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%